Republic of Lithuania : 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
The 2011 Article IV Consultation reports that the economy in the Republic of Lithuania has staged an impressive recovery based on a supportive global environment and determined policy adjustment. The main driver of the recovery was export growth. Executive Directors commended the authorities for Lithuania's impressive economic recovery, noting in particular the sizable fiscal consolidation and the maintenance of confidence in the banking system. Directors also supported the authorities' goal of reducing further the fiscal deficit, thereby putting government debt on a downward path.